Log Data Integrity Solution based on Blockchain Technology and IPFS - Azizi, Yassine; Azizi, Mostafa; Elboukhari, Mohamed (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Threats towards information systems have continued to increase and become more sophisticated, making security approaches a necessity for all types of organizations to ensure their protection. To implement an appropriate computer security policy, it is necessary to efficiently exploit the data that has become a valuable asset for these security systems, provided it is well used, controlled and monitored.In this paper, we focus on developing a decentralized solution based on Blockchain technology and IPFS (InterPlanetary File System) that can maintain and ensure the integrity of log files and sensitive information. The obtained results are promising, we obtained a distributed ledger of all log file transactions in a chronological sequence, which was shared among all Ethereum participants, allowing us to verify the log files’ integrity, validity, and auditability throughout their life cycle.